PENGARUHTIME BUDGET PRESSURE, KOMPLEKSITAS AUDIT, DAN SKEPTISISME PROFESIONAL AUDITOR TERHADAP KUALITAS HASIL PEMERIKSAAN (STUDI EMPIRIS PADA INSPEKTORAT SE-PULAU LOMBOK) - Lalu Agus Sudrajat; Ahmad Rifai; Endar Pituringsih (Jurnal Akuntansi Aktual, 2015)
The purpose of this study is to analyze and to obtain empirical evidence concerning the influence of time budget pressure, the complexity of the audit, and the auditor’s professional skepticism on the quality of examination results of the Inspectorate Local Government in Lombok Island. The number of population in this study is 125 respondents, contain of the auditors and the local governmentsupervisor of the Inspectorate Local Government in Lombok Island, while the number of respondents are 106. Before the hypothesis test, firstly the validity and reliability test is applied, and followed with the classical assumption test and multiple linear regression analysis. The result of this study shows that timebudget pressure, the complexity of the audit, and the auditor’s professional skepticism give positive influence on the quality of the examination results of the Inspectorate Local Government in Lombok Island. Partially complexity of the audit and the auditor’s professional skepticism gives positive influence significantly, whereas time budget pressure has no significant influence. This is caused by theallocation of working hours on overtime hours can be done by the auditor, the auditor’s division of labor based on a fixed object and repeat inspection every year, the inspection team flexibility in audit work program within the budget allotted time, the auditor that the majority of respondents have more than 6 years of experience in the audit, the auditors step of career already arranged in a neat andprofessional education and ongoing training of auditors in the demands of his profession.Keywords: time budget pressure, complexity of the audit, the auditor’s professional skepticism, the quality of examination results